A UTILIZAÇÃO DO TREINAMENTO EAD NAS ORGANIZAÇÕES: UMA INVESTIGAÇÃO SOBRE SUA EFICÁCIA (Revista Interdisciplinar Pensamento Científico, 2021)
The trainment refers to a procedure which aims to improve the worker's learning and to enable him or her to better perform his or her tasks. The trainment absence in the organizations affects thorougly the institution development, and might negatively impact in the processes and results to be achieved, since the workers have not received the necessary capacitation in order to exercise the demanded tasks. The present study aims to evaluate the effects of training adopted by the enterprises and its efficiency in the distance mode. Its analisys is justified by the fact for being an innovative action adopted by many enterprises. The methodology used in the resarch was the bibliographic, available in books, which belong to the chosen area, added by a field research. Therefore, it can be concluded that the trainment in the distance mode becomes efficient when adequate methods and technologies are used.
Keywords: Trainment; Trainment and Development; Distance Trainment.